Columnar microbialites of the upper Miocene of Mallorca (Spain): A new morphogenetic model based on concurrent accretion and bioturbation – uncommon or overlooked?. Issue 1 (14th March 2021) - Suarez‐Gonzalez, Pablo; Benito, M. Isabel; Arenas, Concha; Pomar, Luis
Abstract: Bioturbation has long been considered an antagonist of microbialite development and preservation, because metazoan grazing and burrowing destroy benthic microbial communities. However, metazoan bioturbation, in conjunction with microbial accretion, may have had a significant role in the morphogenesis of some columnar microbialites, as suggested by the case study presented and by some Phanerozoic and Upper Proterozoic analogues discussed here. Late Miocene in age, the studied microbial biostrome developed in a western Mediterranean restricted shallow‐water platform dominated by grainy sediments and with a notable influence of bioturbation. This study is focused on the complex accretionary history of the columnar microbialite biostrome and on its striking dark grey colour, which is attributed to Mn‐oxyhydroxides precipitated during meteoric diagenesis linked to subaerial exposure. The characteristic columnar structure of the microbialite biostrome has features consistent with an accretionary origin of the columns, but also has features suggesting metazoan disruption. Therefore, a new morphogenetic model for columnar microbialites is presented, highlighting the concomitant roles of microbial accretion, bioturbation and grainy sediment infill of the intercolumn space. Whether this model is an exception or a rule, should be tested on other examples of Phanerozoic and Upper Proterozoic columnar microbialites. Nevertheless, this model is a step forward in understanding the complex microbe–metazoan interactions as constructive coexistence rather than just as destructive competition.